Risk Factors Related to COVID-19 Deaths at Fatmawati Hospital in 2021 - Utomo, Muhammad Wiji; Purnamawati, Dewi; Almaududi, Abul A’la; Akaputra, Risky; Sugiatmi, Sugiatmi (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2024)
Background: Coronavirus Disease 2019 (COVID-19) has a risk of death. The risk of death increases in patients with several factors, such as age, gender, and comorbidities. Purposes: This study aims to determine the risk factors for the cause of death in patients with COVID-19 at Fatmawati Hospital in 2021. Methods: This study uses a quantitative approach with a case-control design without matching with a ratio of 1:1. Cases were identified as deaths due to COVID-19 as many as 109, and controls were COVID-19 sufferers who lived or recovered during the treatment period as many as 109 respondents. Data were collected from medical record data and analyzed multivariately with logistic regression. Result: The bivariate modeling showed that Age, Diabetic, Pneumonia, and Acute Respiratory Syndrome (ARDS) have significantly affected COVID-19 mortality (p ≤ 0.05). Multivariate modeling showed the ARDS variable (p=0.0001; OR=53.067) and age variable (p=0.028; OR=2.8) to be risk factors for COVID-19 death at Fatmawati Hospital Jakarta with an Attribute Risk (AR) value of 92,7% and the value of Population Attribute Risk (PAR) 58%. Conclusion: This model can predict 62.1% of COVID-19 deaths; the rest is due to other factors not studied in this study. ARDS is the dominant factor causing the death of COVID-19 at Fatmawati Hospital, Jakarta.